(untitled) (Journal of Forensic Medicine & Toxicology, 2012)
Bitemarks are an important and controversial aspect of forensic odontology. The discipline has received considerable attention in the recent years. The knowledge of the anatomical particularities of human dentition and distribution in the dental arcs can supply subsidies of real value to forensic scientist, sometimes, the only elements on which can count the expert. Particularly, in bite marks found in the skin, generally resultant of rapes, fights, assaults, abuses and child violence, this evidence can mean the crime resolution, assuming a decisive role in the criminal identification. Although there are many cases in which bite mark evidence has been critical to the conviction or exoneration of criminal defendants, there is continuing dispute over its interpretation and analysis. This article gives an overview of bitemarks with special emphasis in their role in forensic identification.